Uji Biolarvasida Ekstrak Metanol Daun Pepaya Jepang pada Larva Anopheles sp. - Dea Farrah Khairunnisa; Emantis Rosa; Priyambodo; Hendri Busman (CV. Multi Kreasi Media, 2026)
Malaria remains a major health problem in endemic areas such as Pesawaran Regency, Lampung, transmitted through the bites of infected female Anopheles mosquitoes. Continuous use of synthetic larvicides may lead to resistance, toxicity to non-target organisms, and environmental pollution, thus safer biolarvicidal alternatives are needed. Japanese papaya leaves (Cnidoscolus aconitifolius) are known to contain secondary metabolites with potential biolarvicidal activity. This study aimed to determine the biolarvicidal activity of methanol extract of Japanese papaya leaves against the mortality of Anopheles larvae and to observe morphological changes in larvae after exposure. The study used a Completely Randomized Design with five treatments: 0% (control), 0.5%, 1%, 1.5%, and 2%, each with five replications. Data were analyzed using one-way ANOVA followed by the Least Significant Difference (LSD) test. Phytochemical screening revealed the presence of alkaloids, flavonoids, saponins, tannins, phenols, and steroids. ANOVA results showed significant differences among treatments (p<0.001), while the LSD test indicated that each concentration had a significantly different effect on larval mortality (p<0.05). The highest mortality was observed at 2% concentration, reaching 82.5% at 24 hours and 100% at 48 hours. The methanol extract also caused morphological damage in larvae, including tissue lysis, digestive tract damage, and respiratory system impairment. It can be concluded that the methanol extract of japanese papaya leaves has potential as a natural biolarvicide against Anopheles larvae.